The Intention to Use Innovative Compliance Application for Thai-Listed Companies - Chalermnon, Pattarasupang; Vuthisopon, Sujira; Saengnoree, Amnuay; Deebhijarn, Samart (Journal of Ecohumanism, 2024)
This study explores the intention to use innovative compliance applications among Thai-listed companies, focusing on a novel technology introduced to companies listed on the Stock Exchange of Thailand (SET). The research employs the Technology Acceptance Model (TAM) as its theoretical foundation, utilizing a quantitative approach. Data from 360 capital market law compliance officers in Thai public companies listed on the SET was analyzed using structural equation modeling. The study identifies four key factors impacting user satisfaction and intention to use the application: perceived ease of use, perceived usefulness, trust, and innovation quality. Results reveal significant relationships between innovation quality, user satisfaction, trust, and the intention to use the application. Findings demonstrate the connection between TAM variables and technology adoption in the legal sector, particularly for capital market law compliance officers. Innovation quality, user satisfaction, and trust emerge as the most influential factors, in that order, affecting the intention to use the application. This research contributes to understanding user perceptions and intentions regarding compliance software, potentially guiding future developments in regulatory technology for Thai-listed companies.